A importância de fatores bióticos no estabelecimento de propágulos em floresta secundária na Amazônia central - Pinto, Marcelo de Figueiredo Pissurno Motta (2017)
The implantation of pasture is the main activity that contributes to deforestation in the Brazilian Amazon, generating incalculable losses in the biodiversity of fauna and flora. The historic of use drive the succession trajectory in the regeneration after the abandonment of these areas. The fire regime for cleaning and maintenance of pastures contributes to the loss of seed and seedlings, sprouts and remanecent individuals. These process favoring only pioneer species capable of withstanding such disturbance, especially of the genus Vismia. In these environments the succession is hampered by the dominance of pioneer species, the absence of dispersant animals and the great presence of predatory animals, limiting the arrival of seeds from the surrounding matrix and establishment of seedlings. Much still needs to be understood with regard to secondary succession processes in these forests. Therefore, this study will seek to describe and understand how and what factors influence and / or prevent three species from the oldgrowth forest (H. courbaril courbaril, O. excelsa excelsa and P. multijuga multijuga) to germinate and establish in areas of capoeira dominated by Vismia in central Amazonia. A direct sowing in the capoeira was done under 3 different treatments, with mosquito net protection, buried and on the litter, in order to exclude seed predation by medium and large terrestrial vertebrates. Another experiment with seedlings of the same species, with and without protection of net, was also set up to evaluate predation and herbivory of large vertebrates at the stage of seedlings. The use of net was crucial in the protection of seeds, since unprotected seeds suffered a high rate of consumption. The net had no difference in the protection of the seedlings, possibly invertebrate animals were the main responsible for the predation of leaves (herbivory), abiotic factors may have been decisived in the establishment of the seedlings, Vismia stands has high luminous incidence, as well as higher temperature and lower humidity, limiting the establishment of shadetolerant species. The lack of dispersant animals and the high population of seed and seedlings predators have also avoid the survival in the early stages of establishment of shade-tolerant species.